Analysis of Compliance Factors in the Use of Personal Protective Equipment and Their Relation to Occupational Diseases among Sasirangan Industry Workers in Banjarmasin City - Nika Sterina Skripsiana; Farida Heriyani; Widya Nursantari; Yulia Syarifa; Siti Habibah Zein; Wahyu Setyaningsih; Fitria Dewi Puspita (Jurnal Berkala Kesehatan, 2026)
Occupational diseases are illnesses caused by work and/or the work environment, which can be experienced by workers in the sasirangan industry. Most sasirangan industry workers in Banjarmasin City do not use personal protective equipment (PPE) while working. The objective of this study was to analyze factors related to PPE compliance and its association with occupational diseases among sasirangan industry workers in Banjarmasin City. This research employed an analytical observational design with a cross-sectional approach, conducted at three sasirangan industry sites in Banjarmasin. Samples were obtained using purposive sampling, with a total of 50 workers. Data were collected through questionnaires. Univariate and bivariate analyses were performed using the chi-square test. The univariate analysis showed that 38% of sasirangan workers had a history of occupational diseases, 58% were non-compliant with PPE use, 32% had poor knowledge regarding PPE, 52% had negative attitudes toward PPE use, and 30% reported the unavailability of PPE in the workplace. The bivariate analysis revealed a significant association between PPE compliance and occupational diseases, as well as between attitudes toward PPE use and PPE availability with PPE compliance, while no significant association was found between knowledge of PPE and PPE compliance among sasirangan industry workers in Banjarmasin City.